Self-concept and self-actualization in the short story Shodiqi Adz Dzill: A review of humanistic psychology - Maulidiyah, Shinta; Yurisa, Penny Respati (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
This study aims to analyze the self-concept and self-actualization contained in the short story Shodiqi Adz Dzill by Arezo Zaenab based on Carl Rogers' humanistic psychology theory. This research uses descriptive qualitative method with Carl Rogers' humanistic psychology theory approach. The data sources in this research are primary data and secondary data. The data collection technique used in this research is reading and writing. From the results of this study, the author found seven data findings which are divided into four components of self-concept, and success in achieving self-actualization, which include: (1) real self, Sarah's attitude that sticks to her perception, (2) ideal self, Sarah tries to accept her mother's views, (3) conditional positive regard, Khadijah accepts Sarah without worrying too much about her behavior, (4) unconditional positive regard, Khadijah accepts Sarah without worrying too much about her behavior, and (5) self-actualization, Sarah overcomes her psychological challenges and reaches her best potential. Based on the results of the above research, it can be concluded that with the acceptance and support of her mother, Sarah managed to overcome these challenges, change her views, by developing to reach her best potential without being afraid of shadows anymore.